Analyzing Risk Factors Associated with Post Myocardial Infarction Complications: A Retrospective Analysis: Post Myocardial Infarction Complications - Muhammad, Tayyeb; Ejaz, Muhammad; Khan, Muhammad Shahid; Zahid, Shahroon; Khan, Sohail; Ali, Ahmed (Pakistan Journal of Health Sciences, 2025)
Myocardial infarction is a major cause of mortality and results in several complications including post-MI arrhythmias, pulmonary edema, and cardiogenic shock. Objective: To evaluate and examine the clinical and demographic factors and their association with post-MI complications. Methods: This was a retrospective observational study and non-probability convenient sampling was recruited for assessment. A total of 188 patients aged 45 to 65 years, hospitalized for acute STEMI and of both genders were included. However, patients with NSTEMI or with comorbidities such as chronic renal failure or cirrhosis were not included. Age, gender, BMI, duration of hospitalization, etc. were recorded on a structured form. Patients were assessed for post-MI arrhythmias, cardiogenic shock, and pulmonary edema. This study took six months its completion. SPSS version 25.0 software was employed for analysis and a chi-square test was used to identify associated risk factors with post-MI complications at a significant level (p<0.05). Results: Findings revealed that the occurrence of post-MI arrhythmias showed a significant association with smoking and family history (p<0.001), while no significant association was observed for BMI, hospital duration, hypertension, or family history. Cardiogenic Shock (CS) is strongly associated with DM (p=0.001) but shows no association with smoking, BMI, duration of hospital stays, hypertension, or family history. Conclusions: Smoking and a family history of cardiovascular disease are prevalent and found significant association with post-MI arrhythmias (p<0.001) after myocardial infarction; diabetes mellitus also resulted in significant association with pulmonary edema and cardiogenic shock (p<0.001).